Persistent idiopathic facial pain associated with borderline personality disorder: a case report - Martins, Hugo Andre de Lima; Martins, Bruna Bastos Mazullo; Santos, Camilla Cordeiro dos; Pontes, Djanilson Jose; Oliveira, Daniella Araújo de; Valença, Marcelo Moraes (Headache Medicine, 2021)
Introduction Borderline personality disorder may be associated with persistent facial pain since its relationship with different pain syndromes has been reported. Persistent idiopathic facial pain is commonly unilateral, pulsating, burning, or profound and challenging for clinicians. Therefore, excluding underlying organic causes by appropriate clinical investigation and complementary tests is essential to diagnose this disease. Objective This case report aimed to provide evidence of the relationship between idiopathic persistent facial pain and borderline personality disorder. Case report A 24-year-old woman reported severe pain in the left hemiface for ten months, three to six hours per day, five days per week. No abnormalities were found in dental and neurological assessments. A psychiatric evaluation was performed, and the patient met the criteria for borderline personality disorder. Pharmacological treatment consisted of daily lithium carbonate (900 mg) and venlafaxine (150 mg). Weekly sessions of cognitive-behavioral therapy with emotional regulation and tolerance to stress were performed. The patient was evaluated every 30 days and showed improved pain intensity and frequency over six months. Conclusion Proper management of borderline personality disorder can modify the evolution of persistent idiopathic facial pain when both pathologies are comorbidities.